Results of thrombolytic treatment with recombinant streptokinase in elderly and non elderly patients. - René Tomás Manso Fernández; Francisco Valladares Carvajal; Claudio González Rodríguez.; Marcos D. Iraola Ferrer (Medisur)
Fundament: The great advances of modern medicine in the last 30 years, have deepened on the treatment of acute myocardial infarct dynamically and efficiently, allowing at present to show good results not only in the decrease of the mortality rate but also in the improvement of the patientâ?Ts quality of life. Objective: To offer the precise results with recombinant sterptokinase in elder and non-elder patients with an acute myocardial infarct. Method: prospective observational study of 325 patients admitted with a diagnosis of an acute myocardial infarct at the ¨Dr. Gustavo Aldereguia Lima¨ Hospital. These patients received thrombolitic treatment with recombinant strptokinase (Heberkinase) i a dose of 1 500 000 units, and treatment with 325 mg of acetil salicilic acid too. Results: The presence of the infarct was more frequent in males (68,31%) mainly associated to the smoking habit, Hypertension, and cholesterolemia in patients less than 74 years of age and in those patients aged 75 or more, the infarct was associated to Hypertension and Diabetes. The most affected side of the heart was the anterior part(44,6%), and the thrombolitic treatment was developd in an average of 211, 76 minutes. Deaths increased with age. The most significant variables associated to mortality in the infarcted patients were the fact of being hemodinamically classified into a Killip-Kimball (K-K) Grade III-IV and having had arrhythmia and cardiac rupture.